1994
DOI: 10.1128/jvi.68.1.575-579.1994
|View full text |Cite
|
Sign up to set email alerts
|

Use of random systematic mutagenesis to generate viable human rhinovirus 14 chimeras displaying human immunodeficiency virus type 1 V3 loop sequences

Abstract: Random systematic mutagenesis was used to generate a library of human rhinovirus 14 chimeras that each display a segment from the V3 loop of human immunodeficiency virus type 1. The sequence XXIGPGRAXX, where X could be any of the 20 amino acids, was inserted at the neutralizing immunogenic site II of human rhinovirus 14 between VP2 residues 159 and 160. Twenty-five unique chimeric viruses were isolated, and the identity of their randomized residues was determined. A nonrandom amino acid distribution that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…Lastly, in contrast to the rhinovirus that lacks this capacity, the Ad platform has sufficient coding capacity allowing for HIV-1 transgene expression in combination with presenting the same or a different antigen on the viral capsid surface. Despite some of the noted limitations with the rhinovirus platform, one of its attractive features has been the previously mentioned development of mutagenic libraries of human rhinovirus 14 chimeras that each display randomized residues representing HIV-1 V3 or MPER epitopes [48,49]. In this regard, it is worth mentioning that our lab has previously developed a similar approach for screening and identifying heterologous amino acid sequence insertions which have been incorporated into the adenovirus fiber knob region using a modified phage display approach [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, in contrast to the rhinovirus that lacks this capacity, the Ad platform has sufficient coding capacity allowing for HIV-1 transgene expression in combination with presenting the same or a different antigen on the viral capsid surface. Despite some of the noted limitations with the rhinovirus platform, one of its attractive features has been the previously mentioned development of mutagenic libraries of human rhinovirus 14 chimeras that each display randomized residues representing HIV-1 V3 or MPER epitopes [48,49]. In this regard, it is worth mentioning that our lab has previously developed a similar approach for screening and identifying heterologous amino acid sequence insertions which have been incorporated into the adenovirus fiber knob region using a modified phage display approach [50][51][52].…”
Section: Discussionmentioning
confidence: 99%
“…The human rhinovirus has been utilized for HIV vaccination in the context of the antigen capsid-incorporation strategy. Researchers have constructed human rhinovirus: HIV chimeras to stimulate immunity against HIV-1 [79]. As well, researchers have designed combinatorial libraries of human rhinovirus capsid incorporated HIV-1 glycoprotein 41 (gp41) epitope, eliciting antibodies whose activity can mimic the NAb effect [80].…”
Section: Antigen Capsid-incorporation Strategies For Vaccination Schemesmentioning
confidence: 99%
“…Commercial and clinical development of Ad-based HIV vaccines has progressed faster than the development of vector systems such as human rhinovirus because the tremendous flexibility of Ad generally exceeds that of current rhinovirus systems. For instance, since human rhinovirus is a relatively small RNA virus, the human rhinovirus platform can only display 60 copies of a single HIV-1 epitope [79]. In contrast, the Ad vector capsid platform could allow incorporation of HIV-1 epitopes into 4 structurally distinct domains including hexon [81], fiber, penton base, and protein IX (pIX), similar to the illustration depicted in Figure 1 [82,83].…”
Section: Antigen Capsid-incorporation Strategies For Vaccination Schemesmentioning
confidence: 99%
“…Research groups have constructed human rhinovirus:HIV-1 chimeras in an effort to stimulate immunity against HIV-1. 148,253 In an effort to develop HIV-1 vaccines, researchers within this same group generated combinatorial libraries of HRV capsid-incorporated HIV-1 gp41 epitope. Their results indicated that they were successful in eliciting antibodies whose activity can mimic the Nab effect.…”
Section: Dovepressmentioning
confidence: 99%
“…For example, because HRV is a relatively small RNA virus, the HRV platform can display an array limited to 60 copies of a single HIV-1 epitope. 148,253 In contrast, the Ad vector platform allows incorporation of the HIV-1 MPER epitope into three structurally distinct locales, including HVR2, HVR5, 247 and protein IX (our unpublished data). In comparison, the Ad MPER antigen capsid-incorporation display platform could present an array of 720 HIV-1 epitope copies within Ad hexon and 240 HIV-1 epitope copies within pIX.…”
Section: Dovepressmentioning
confidence: 99%